Effects of Increasing Lactose with or without Pharmacological Levels of Zinc on Performance, Fecal Dry Matter, and Plasma Zinc Concentration in Nursery Pigs - Joana Magoga; Julian Arroyave; Jordan T. Gebhardt; Robert D. Goodband; Jason C. Woodworth; Joel M. DeRouchey; Katelyn N. Gaffield; Mike D. Tokach (Kansas Agricultural Experiment Station Research Reports, 2025)
A study was conducted to evaluate the interactive effects of dietary lactose concentration and pharmacological levels of added Zn on growth performance, fecal DM, and plasma Zn concentrations in nursery pigs. At weaning, 360 pigs (initially 13.0 ± 0.24 lb) were randomly allotted within three body-weight blocks to one of six dietary treatments in a randomized complete block design. The study was arranged as a 2 × 3 factorial with main effects of added Zn (110 vs. 3,000 mg/kg Zn from ZnO) and three lactose concentrations: high (20% in phase 1 and 10% in phase 2), medium (10% in phase 1 and 5% in phase 2), and low (5% in phase 1 and none in phase 2). Experimental diets were fed for 21 d (phases 1 and 2), followed by a common diet fed for an additional 21 d (phase 3). There were five pigs per pen and 12 replicate pens per treatment. No lactose × Zn interactions were observed for growth performance (P > 0.10). From d 0 to 21, pigs fed pharmacological levels of Zn had improved (P ≤ 0.007) ADG, ADFI, and F/G compared with pigs fed low Zn diets. Increasing lactose increased (linear, P = 0.048) BW on d 21. However, from d 0 to 42, ADG, ADFI, F/G, and d 42 BW were unaffected by increasing lactose or Zn. There were no lactose × Zn × day interactions for fecal DM, although pigs fed pharmacological Zn tended to have decreased fecal DM on both d 10 and 21 (P ≤ 0.078). For plasma Zn, a linear lactose × Zn × day interaction (linear, P = 0.004) was observed. On d 10, but not d 0 or 21, plasma Zn concentration was greater in pigs fed 3,000 mg/kg of Zn when fed high lactose and declined as the lactose level decreased. In contrast, in pigs fed 110 mg/kg of Zn, the plasma Zn remained relatively low across lactose levels. For the main effect of Zn, on both d 10 and 21, pigs fed 3,000 mg/kg of Zn had greater (P < 0.001) plasma Zn concentrations compared to those fed 110 mg/kg of Zn. In conclusion, pharmacological levels of Zn improved early nursery growth performance and influenced plasma Zn concentrations; however, these benefits did not persist throughout the overall 42-d period. Increasing lactose improved the feed intake and early body-weight gains during phase 1 but had a limited impact on overall performance.
Keywords: growth performance; fecal dry matter; lactose; nursery pigs; plasma Zn; Zn oxide